If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5z + 3z + -7 = 8z + -1 + -6 Reorder the terms: -7 + -5z + 3z = 8z + -1 + -6 Combine like terms: -5z + 3z = -2z -7 + -2z = 8z + -1 + -6 Reorder the terms: -7 + -2z = -1 + -6 + 8z Combine like terms: -1 + -6 = -7 -7 + -2z = -7 + 8z Add '7' to each side of the equation. -7 + 7 + -2z = -7 + 7 + 8z Combine like terms: -7 + 7 = 0 0 + -2z = -7 + 7 + 8z -2z = -7 + 7 + 8z Combine like terms: -7 + 7 = 0 -2z = 0 + 8z -2z = 8z Solving -2z = 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. -2z + -8z = 8z + -8z Combine like terms: -2z + -8z = -10z -10z = 8z + -8z Combine like terms: 8z + -8z = 0 -10z = 0 Divide each side by '-10'. z = 0.0 Simplifying z = 0.0
| 3x-2=4x-8 | | 7n^2-43n+6=0 | | n^2=n | | 7p^2-27p-40=0 | | 5a=20 | | -7=2y-3-3y | | 3x-7(-2x+8)=-5 | | 3x-7y=-5 | | 10n+8p=0 | | S=3t+40 | | (x-1)+(x+3)=2x | | k-8(7+k)=-1(5) | | 4t-3-3t=-5 | | 9x+3y=4 | | (3x+4)(2-5x)=0 | | c=(2)(3.14)(r) | | 9x-4y=-2 | | 6.3y=4.1y+12 | | 1.2=1.6m | | c=23 | | -8=5a-3a | | -54=133.578499968x+0.5*0.0209625668*17843.21565 | | 6(x+2)-(3x-8)= | | 4(x+3)-(2x-4)= | | 54=133.578499968x+0.5*0.0209625668*17843.21565 | | 3b+(4b-6b+2)-b=10 | | 13t^2-10t+2=0 | | 11t-8t=-3 | | 11=x-(-9) | | 7*x-2=0 | | x(2)+3=x | | -9(12)*15(145)+4b=3 |